2017
DOI: 10.21608/adjalexu.2017.57852
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Dental Interns Towards Learning Communication Skills in Alexandria University

Abstract: INTRODUCTION: Effective communication not only improves dentist-patient relationships, but also enhances the patient's satisfaction towards the profession. Dental students are generally receptive to learning communication skills during their academic education and their appreciation for the value of these skills can be significantly improved with training. OBJECTIVES: The objective of this study was to compare the attitudes of dental interns towards learning communication skills at both Faculty of Dentistry Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
3
2
Order By: Relevance
“…This is in accordance with the results of a study conducted in Nepal on a sample of medical students which found no statistically significant relationship between gender and positive attitudes towards learning communication skills (Shankar et al, 2013). However, this was in contrast to the earlier study conducted by (Atteya et al, 2017) where they found that female interns had higher PAS scores than male interns. Roter and Hall (Roter & Hall, 1998)explained the effect of gender on the physician-to-patient relationship as that may be because the art of communication originates more naturally from a female, so she may be more likely to appreciate the importance of physician to patient communication.…”
Section: Methodscontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with the results of a study conducted in Nepal on a sample of medical students which found no statistically significant relationship between gender and positive attitudes towards learning communication skills (Shankar et al, 2013). However, this was in contrast to the earlier study conducted by (Atteya et al, 2017) where they found that female interns had higher PAS scores than male interns. Roter and Hall (Roter & Hall, 1998)explained the effect of gender on the physician-to-patient relationship as that may be because the art of communication originates more naturally from a female, so she may be more likely to appreciate the importance of physician to patient communication.…”
Section: Methodscontrasting
confidence: 99%
“…This is very similar to Richa et al, 2016(Richa et al, 2016 where they reported scores of 50.44 ± 5.83 and 29.72 ± 4.32, respectively. These results are also in accordance with a study conducted in Alexandria in Egypt evaluating the dental interns' attitudes toward learning communication skills where the mean PAS score was 52/65 (Atteya et al, 2017). For individual questions, an average score of more than 2.5 out of 5 on the Likert scale indicated a trend whether the students were against or with the question.…”
Section: Methodssupporting
confidence: 90%
“…It is noted that these two subscales construct the social skills branch of a person's whole EI (1). A recent study in 2016, in Alexandria University, by Atteya et al (30), reported that dental interns showed positive attitudes towards learning communication skills, it was also noticed that students have been learning communication skills through lectures incorporated into their dental public health curriculum; this could have taught them how to manage people's emotions through effective communications. Moreover, during the clinical years of study, participants might have experienced handling patients who were anxious or in pain, and this could have enhanced their awareness of people's emotions in addition to managing them at such emotionally stressful situation.…”
Section: Discussionmentioning
confidence: 99%
“…A study on dental interns reported that females and those with training in communication skills were associated with positive attitudes towards learning communication skills [9]. Another study concluded that dentists, patients, and students contemplate professional communication skills are important in the dentist-patient relationship [10].…”
Section: Introductionmentioning
confidence: 99%